Fear responses to safety cues in anxious adolescents: preliminary evidence for atypical age-associated trajectories of functional neural circuits - Haddad, Anneke D.M.; Bilderbeck, Amy; James, Anthony C.; Lau, Jennifer Y.F. (Elsevier, 2015)
Adolescent anxiety is common and impairing and often persists into adulthood. There is growing evidence that adult anxiety is characterized by abnormal fear responses to threat and safety cues, along with perturbations in fear-related neural circuits. Although some of this work has been extended to adolescents, with promising results, it is not yet clear whether changes in these circuits across developmental age varies between anxious and non-anxious adolescents. Here we used fMRI to examine how age modulates neural responses as adolescents are exposed to threat and safety cues. Participants were 15 anxious and 11 non-anxious adolescents (age 12-17) who completed a fear conditioning paradigm. The paradigm incorporated a threat cue comprising a neutral face which was paired with a fearful, screaming face, a safety cue comprising a different neutral face, and a control stimulus. Across the whole sample, neural activation to the threat cue (relative to the control cue) correlated positively with age in a number of regions, including the dorsal anterior cingulate and bilateral dorsolateral prefrontal cortex (PFC). However, neural activation to the safety cue (relative to the control cue) was modulated differently by age in the two groups: a more positive association between activation and age was observed in the control group compared to the anxious group in various regions including medial and dorsolateral PFC, anterior insula, and amygdala. These findings suggest that maturation of the neural substrates of fear responses to safety cues may be perturbed in anxious adolescents, potentially contributing to the emergence and maintenance of anxiety disorders in adulthood.